Single-and Multi-Joint Maximum Weight Lifting Relationship to Free-Fat Mass in Different Exercises for Upper-and Lower-Limbs in Well-Trained Male Young Adults - Massini, Danilo A. [UNESP]; Macedo, Anderson G. [UNESP]; Almeida, Tiago A. F. [UNESP]; Espada, Mário C.; Santos, Fernando J.; Castro, Eliane A. [UNESP]; Ferreira, Daniel C. P. [UNESP]; Neiva, Cassiano M. [UNESP]; Pessôa Filho, Dalton M. [UNESP] (MDPI, 2022)
This study aimed to analyze whether the relationship between regional and whole-body fat-free mass (FFM) and strength is related to FFM distribution and area according to limb involvement. Thirty well-trained male young adults underwent one-repetition maximum test (1RM) to assess the strength in arm curl (AC), bench press (BP), seated row (SR), leg press 45◦ (LP45), knee extension (KE), and leg curl (LC). Dual-energy X-ray absorptiometry was used to evaluate FFM. The values for 1RM in AC, BP, and R correlated to FFM in upper limb (R2 = 0.69, 0.84 and 0.75), without an effect of appendicular mass index (API) or area. For 1RM in KE, the correlation with FFM in lower limb increased with thigh area (R2 = 0.56), whereas 1RM in LC and LP45 correlation to whole-body FFM increased with API (R2 = 0.64 and 0.49). The upper limb’s FFM may be reliable for indexing the arms and upper trunk strengths, whereas the relationships between FFM and strength in lower limb improve as muscle mass and thigh area increases between subjects.
Keywords: body composition; early adulthood; muscle strength; resistance exercise